SEMPRONIO ASELIÓN Y SU LUGAR EN LA HISTORIOGRAFÍA ROMANA. UNA REVISIÓN DEL PROBLEMA - López López, Matías (Myrtia, 1995)
This work attempts to demonstrate, according to a new analysis of the texts, the main role played by Sempronius Asellio in the evolution of Roman historiography. Special attention is payed to Cicero's viewa about history and historians in order to understand the writer Asellio and his true contribution to historical genre.